Sea Surface Temperature Reconstruction Period 1993 - 2007 Based on Content Analysis of Coral Sr/Ca from the Region Labuan Bajo, Simeulue Island - Sri Yudawati Cahyarini (Indonesian Journal on Geoscience, 2011)
DOI: 10.17014/ijog.v6i3.121Sea surface temperature (SST) is one of the important parameters for (paleo) climate studies. The long time series of SST data are required to understand more the climate change. Coral geochemical proxy such as Sr/Ca overcomes this problem. Coral can provide long time series of climate data continuously from present till hundreds years ago, even fossil (dead) coral can do it till thousand years ago. In this study, Sr/Ca content of Porites coral within 10 m deep from Labuan Bajo, Simeulue Island was analyzed to reconstruct SST. Coral Sr/Ca shows a strong correlation with local SST in seasonal scale as well as in the annual mean scale. Reconstructed SST data show that the monsoon between 1993 2007 strongly influence the SST variation in the Simeulue region. It supposed that the seasonal variation signal strongly influence local SST than the annual mean signal such as El Nino.